Effects of mycophenolate mofetil introduction in liver transplant patients: results from an observational, non-interventional, multicenter study (LOBSTER) - Schlitt, Hans Jürgen; Jonas, Sven; Ganten, Tom M.; Grannas, Gerrit; Moench, Christian; Rauchfuss, Falk; Obed, Aiman; Tisone, Giuseppe; Pinna, Antonio D.; Gerunda, Giorgio E.; Beckebaum, Susanne (Clinical transplantation, 2013)
The benefits of calcineurin inhibitor (CNI)-sparing regimens on renal function following liver transplantation (LT) have been demonstrated in clinical studies. This observational study assessed the real-life effects of mycophenolate mofetil (MMF) introduction in LT patients. Four hundred and ninety-seven patients in whom MMF was introduced according to local standards or clinical considerations were entered. Patients were grouped by time between transplantation and start of MMF (start of study): Group A (n = 263): ≤6 d; Group B (n = 64): >6 d to ≤1 month; Group C (n = 74): >1 month to ≤1 yr; and Group D (n = 96): >1 yr. CNI sparing occurred in all groups, particularly in Groups C and D. Mean MMF doses at 12 months were 1202.7, 1363.5, 1504.7, and 1578.1 mg/d, respectively, in Groups A-D. At introduction of MMF, median glomerular filtration rate was 73.3, 81.7, 62.7, and 53.7 mL/min/1.73 m2 in Groups A-D. At 12 months, this decreased to 66 mL/min/1.73 m2 in Groups A and B, remained stable in Group C, and increased in Group D (64.8 mL/min/1.73 m2). Serious adverse drug reactions were lowest in Group D. In conclusion, MMF with a subsequent decrease in CNI was well tolerated and improved renal function even years after transplantation. A more forceful MMF dosing strategy with greater CNI sparing may further improve renal function.